2015
DOI: 10.1152/ajplung.00298.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase-induced elastin degradation mediates macrophage influx and lung injury in 60% O2-exposed neonatal rats

Abstract: Neutrophil (PMNL) influx precedes lung macrophage (LM) influx into the lung following exposure of newborn pups to 60% O2. We hypothesized that PMNL were responsible for the signals leading to LM influx. This was confirmed when inhibition of PMNL influx with a CXC chemokine receptor-2 antagonist, SB-265610, also prevented the 60% O2-dependent LM influx, LM-derived nitrotyrosine formation, and pruning of small arterioles. Exposure to 60% O2 was associated with increased lung contents of neutrophil elastase and α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, this was not the case with normobaric hyperoxia-based models in mice, where many reports also confirm that Eln mRNA levels were up-regulated by hyperoxia exposure, but there appeared to be a paucity of lung insoluble elastin, when (iso)desmosine was used as a surrogate for mature, insoluble elastin fibers ( 89 , 96 ). However, these observations are complicated by other reports of increased elastin protein in the hyperoxia models, employing either slot–blots ( 98 ) or immunoblots ( 51 , 93 ). This controversy must still be resolved.…”
Section: Key Structural Components Of the Ecm: Collagen And Elastinmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this was not the case with normobaric hyperoxia-based models in mice, where many reports also confirm that Eln mRNA levels were up-regulated by hyperoxia exposure, but there appeared to be a paucity of lung insoluble elastin, when (iso)desmosine was used as a surrogate for mature, insoluble elastin fibers ( 89 , 96 ). However, these observations are complicated by other reports of increased elastin protein in the hyperoxia models, employing either slot–blots ( 98 ) or immunoblots ( 51 , 93 ). This controversy must still be resolved.…”
Section: Key Structural Components Of the Ecm: Collagen And Elastinmentioning
confidence: 95%
“…In support of this idea, transgenic over-expression of elafin in the vascular endothelium similarly protected mice against the aberrant alveolarization and perturbed elastin assembly caused by mechanical ventilation ( 101 ). Subsequent exciting work by Keith Tanswell’s group has similarly reported that neutrophil elastase inhibition with sivelestat also improved lung structure and elastin deposition in the hyperoxia-based BPD animal model in mice ( 98 ). In this study, it is also noted that administration of anti-elastin antibodies in the mouse hyperoxia model of BPD prevented inflammatory infiltration into the lungs.…”
Section: Key Structural Components Of the Ecm: Collagen And Elastinmentioning
confidence: 99%
“…The effect of elastase on expression levels of alveolar Type I and II markers may be explained via several mechanisms. First, elastase-induced elastin fragments are known chemokines for macrophages in an adult murine model of emphysema, and elastin fragments can impair alveologenesis (Houghton et al, 2006; Masood et al, 2015). Second, mechanical stimuli are well-known to affect proliferation and differentiation of stem cells (Shah et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil elastase and cathepsin G belong to the PA clan, based on their 3D structure (double β barrel fold) and catalytic triad formed by Histidine (His), Asparagine (Asp), and Serine (Ser) residues [ 31 , 32 ]. Substrates cleaved by neutrophil elastase and cathepsin G include proteins involved in maintaining the integrity of the extracellular matrix such as fibronectin, laminin, and proteoglycans [ 33 35 ]. Neutrophil elastase also cleaves elastin and collagens [ 35 ].…”
Section: Discussionmentioning
confidence: 99%